Empowering future generation with renewable solar energy: a conceptual paper / Alya Atrisyia Azizi Khairul ... [et al.] - Azizi Khairul, Alya Atrisyia; Mazlan, Muhammad Farid; Nor Azlan, Maisarah; Ramli, Suriana (2022)
The government announcement of 100% elimination of taxes on electronic vehicles in Malaysia is aligned with the 12th Malaysian Plan which is to achieve carbon neutrality by 2050. It is the Malaysian government's strategic plan that the new policy would accelerate the development of the Electronic Vehicle (EV) industry. Currently, Malaysia is still way behind its regional peers when it comes to the infrastructure of the EV industry in which the available EV charging stations are still solely dependent on electricity. Malaysia is highly dependent on traditional electricity which relies heavily on fossil fuels. Understanding the potential of the solar renewable energy in the EV industry in Malaysia, the research proposed two objectives. The first objective is to broaden the usage of renewable energy in Malaysia to reduce the dependence on fossil fuels. The second objective is to enhance the usage of electric vehicles in Malaysia by 2050. The study propose that the success of the renewable solar energy program would be highly dependent on the collaboration of government, private solar companies and the major supplier of electricity. The significance of the research to the society and government is that it provide a comprehensive framework that would enable the development of accessible infrastructure of EV charging ports near residential areas or at the local gas station. An accessible charging port may ease market acceptance on the usage of electric vehicles. The increase of EV usage would reduce the reliance on fossil fuels and in the long run would protect the environment. The development of solar renewable energy should remain one of the essential parts of the economic development in Malaysia. In time, the usage of EV will be in mass and it is important for the country to have the best infrastructure to support the growth of the industry.